2008
DOI: 10.1002/jctb.1954
|View full text |Cite
|
Sign up to set email alerts
|

Sequential batch reactor for eucalypt kraft pulp effluent treatment with Trametes versicolor

Abstract: BACKGROUND: A sequential batch reactor (SBR) was used for eucalypt kraft pulp effluent treatment with Trametes versicolor. A 2 3 full factorial design and response surface methodology were applied to optimise the batch fermentation conditions. Effluent concentration, culture medium and inoculum age were the factors selected for this study in order to optimise the reduction of chemical oxygen demand (COD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…With improved pH stability and thermal stability, laccase from the mutant S152 would be more suitable for biotechnological and environmental applications, such as decoloration of waste water from textile (under neutral or alkaline pH conditions), pulp delignification, and biotransformation [3,5]. …”
Section: Effect Of Ph and Temperature On Enzyme Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…With improved pH stability and thermal stability, laccase from the mutant S152 would be more suitable for biotechnological and environmental applications, such as decoloration of waste water from textile (under neutral or alkaline pH conditions), pulp delignification, and biotransformation [3,5]. …”
Section: Effect Of Ph and Temperature On Enzyme Stabilitymentioning
confidence: 99%
“…Their wide substrates spectrum allows laccases to be extensively used in various areas such as pulp delignification, dye decoloration, environmental pollutant detoxification, biopolymer modification, biotransformation, and food dechlorination [1,[3][4][5][6][7]. However, industrial applications of laccases are usually hindered by their long fermentation period, low laccase yield, as well as poor enzyme stability.…”
Section: Introductionmentioning
confidence: 99%
“…Laccases (benzenediol:oxygen oxidoreductases, EC 1.10.3.2) are multicopper oxidase enzymes, being characterized by high activity and remarkable ability to oxidize a wide range of substrates, including phenolic compounds [1][2][3]. Due to these advantageous properties, numerous potential industrial applications have been reported [4] for such enzymes, like dye decolourization [5][6][7], pulp delignification [8,9], soil bioremediation [2,10], and detection of specific analytes [10].…”
Section: Introductionmentioning
confidence: 99%
“…When other substrates are not available, the role of these enzymes on woods is the delignification of hemicelluloses by oxidative reactions in order to ensure survival of these carbon staffs. The biocatalytic potential of T. versicolor has been studied for different industrial applications such as bleaching of Kraft pulps [17,18], effluents decolorization and biotreatment [19] and also to find out oxidation mechanisms with lignin models [20,21]. This fungus is also reported to be a medicinal fungus producing an exopolysaccharide with antitumor activity when it is grown in specific experimental conditions [22].…”
Section: Introductionmentioning
confidence: 99%